Improving hemodynamics – Prolonged intra-aortic balloon pump usage in posterior ventricular septal rupture with right ventricle dysfunction - Karthik Raman; Thapo T Desugari; S Sowmya; Samuel S Angula; Kalaichelvan Uthayakumaran; Anbarasu Mohanraj (Annals of Cardiac Anaesthesia, 2020)
The associated mortality and morbidity of posterior ventricular septal rupture (VSR) is quite high increasing to almost 80% due to severe right ventricle dysfunction and pulmonary artery hypertension. Herein, we present a case of posterior VSR due to inferior wall myocardial infarction who underwent surgery. Premature removal of intra-aortic balloon pump (IABP) led to hemodynamic deterioration and he was salvaged with prolonged and prompt re-institution of IABP. This case also highlights the importance of IABP in right ventricle failure.